Разработка и исследование макета системы активного экранирования магнитного поля, создаваемого группой воздушных линий электропередачи - Кузнецов, Б.И.; Никитина, Т.Б.; Бовдуй, И.В.; Волошко, А.В.; Виниченко, Е.В.; Кобылянский, Б.Б. (Електротехніка і електромеханіка, 2018)
Разработан макет одноконтурной системы активного экранирования магнитного поля, создаваемого в жилом помещении группой ЛЭП. Пространственное расположение и геометрические размеры компенсирующей обмотки, а также параметры регуляторов определены на основе решения задачи многокритериальной оптимизации. Проведены полевые экспериментальные исследования макета системы с разомкнутым и замкнутым управлением. Показано, что эффективность системы при разомкнутом и замкнутом управлении примерно одинаковая и составляет более 4 единиц. Приведены результаты сравнения экспериментальных и расчетных значений индукции магнитного поля в зоне экранирования. Показано, что экспериментальные и расчетные значения индукции магнитного поля отличаются не более чем на 20 %. Розроблено макет одноколової системи активного екранування магнітного поля, яке створюється у житлових приміщеннях групою ЛЕП. Просторове розташування і геометричні розміри компенсуючої обмотки, а також параметри регуляторів визначені на основі рішення задачі багатокритеріальної оптимізації. Проведено польові експериментальні дослідження макету системи з розімкнутим та замкнутим управлінням. Показано, що ефективність системи при розімкнутому та замкнутому управлінні приблизно однакова і складає більше 4 одиниць. Наведено результати порівняння експериментальних і розрахункових значень індукції магнітного поля в зоні екранування. Показано, що експериментальні і розрахункові значення індукції магнітного поля відрізняються не більше ніж на 20 %. Purpose. Development and field experimental research of layout of the single-circuit active screening system of the magnetic field generated by group of high voltage transmission lines in residential area is given. Methodology. Mathematical model of magnetic field, generated by group of high voltage transmission lines in residential area, based of the experimental values of magnetic field flux density in given points on the basis of optimization problem solving is improved. The objective of the synthesis of the single circuit active screening system is to determine their number, configuration, spatial arrangement, wiring diagrams and compensation cables currents, setting algorithm of the control systems as well as the resulting value of the magnetic flux density at the points of the protected space. Synthesis of the full-scale model of active screening system is reduced to the problem of multiobjective nonlinear programming with constraints in which calculation of the objective functions and constraints are carried out on the basis of the Maxwell equations solutions in the quasi-stationary approximation. The problem is solved by a stochastic multiswarm multi-agent particles optimization. Results. The single-circuit active screening system synthesis results for reduction of a magnetic field generated by group of high voltage transmission lines in residential area is given. Field experimental researches of the single-circuit active screening system of the magnetic field generated by group of high voltage transmission lines in residential area with various control algorithms is given. Originality. For the first time out the development and field experimental studies of the single-circuit active screening system of the magnetic field generated by group of high voltage transmission lines in residential area are carried out. Practical value. Practical recommendations on reasonable choice of the spatial arrangement of compensating cables of single-circuit active screening systems of the magnetic field generated by group of high voltage transmission lines is given. Results of field experimental investigations of the single-circuit active screening system of the magnetic field generated by group of high voltage transmission lines in residential area are given